Pendapat Hukum (Legal Opinion) dan Uji Kepatutan Dari Segi Hukum (Legal Due Diligence) - Syahrul Sitorus (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
For the legal interests of his clients, an advocate must understand the position of the case experienced by his client, for which honest information from the client is needed, both in writing and verbally with the intention that advocates in providing legal advice. Legal opinion cannot be separated from the existence of interview processes, legal audits and legal reasoning that are converged with material that is so complex because it does not only involve legal studies but also cross scientific disciplines to obtain legal aspects or information regarding legal or legal events certain. The Advocate's statement which provides legal opinion based on information, facts and documents given to the Advocate is limited to the date the said legal opinion is signed by the Advocate in question